Laws for the Government of the City of Raleigh 63 (1854) - (:unkn) unknown (My University, 1854)
§ 6: No person shall discharge any gun or other fire-arms within any of the streets or public squares of the city, or upon any lot of the same, (excepting his own lot,) on pain of forfeiting four dollars for every such offence. Or, if the offence be committed in the night, the offender shall forfeit twenty-five dollars
Keywords: DISCHARGE